Evaluation of approaches to the regulation of digital film distribution - A. R. Akopyan; A. M. Arakelyan; Yu. V. Vorontsova; V. V. Krysov (Вестник университета)
The article considers approaches to the state regulation of digital film distribution, evaluates them. The paper generalizes them in the form of proposals for anti-piracy regulation, promotion of original content of online cinemas in international markets, as well as for effective interaction of online cinemas with the Ministry of Culture and the Cinema Foundation. This will resolve the issue of serious competition to traditional cinemas, since the viewer has the opportunity to watch their favorite films without leaving home, and also related to the start of work on their own exclusive content of a large number of digital platforms. The state obliges digital platforms to provide information about the number of views of their content in a single automated information system. This information helps to assess the effectiveness of budget support for cinema, since there are examples of films that did not collect a large box office at the box office but were able to gain more than one million views on the Internet.